2020
DOI: 10.1016/j.soildyn.2020.106165
|View full text |Cite
|
Sign up to set email alerts
|

Seismic fragility analysis of shear-critical concrete columns considering corrosion induced deterioration effects

Abstract: Shear-critical reinforced concrete structures such as older columns with insufficient transverse reinforcement details or short columns are found to be vulnerable to earthquake loading. Meanwhile, in the aggressive environment, RC structures tend to be more vulnerable to earthquake since corrosion of reinforcements will cause deterioration of the material properties. In the present study, a new framework is proposed for seismic fragility analysis of shear-critical structures with the consideration of corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…Fan et al [ 12 ] established a fragility analysis framework for RC bridge structures subjected to the multi-hazard effect of vessel collisions and corrosion. Meanwhile, the modeling and analysis of the time-dependent seismic fragility due to the corrosion effects of RC bridges has received significant attention [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fan et al [ 12 ] established a fragility analysis framework for RC bridge structures subjected to the multi-hazard effect of vessel collisions and corrosion. Meanwhile, the modeling and analysis of the time-dependent seismic fragility due to the corrosion effects of RC bridges has received significant attention [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to China’s Ministry of Transportation, the aging and deterioration phenomenon of MSC concrete girder bridges are commonly found in seismic zones, such as northern China, because deicing salts are extensively used on highway bridges [ 24 ]. The existing contributions [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] also indicated that RC bridges subjected to the mechanisms of corrosion deterioration might be more vulnerable to earthquake hazards. Moreover, since previous studies [ 25 , 26 ] demonstrated that chloride from deicing salts can cause more degradation of bridges than that in a marine environment, the impacts of corrosion degradation due to chloride-laden deicing salts should be researched in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional seismic fragility curves based on a scalar intensity measure (IM) have been widely used to generate fragility estimates in earthquake events (Hwang et al, 2001;Baker and Cornell, 2005;Cimellaro et al, 2010;Xu et al, 2020a). Although they are affected by geometry and material uncertainties, seismic fragility estimates are dominated by the earthquake uncertainty (Kwon and Elnashai, 2006;Padgett and DesRoches, 2007;Jalayer et al, 2014;Mangalathu et al, 2018;Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of the mechanical properties of both steel bars and concrete comprises several corrosion effects that reduce the seismic performance levels of the corroded reinforced concrete (RC) members. Therefore, analytical and empirical models have been widely developed to predict the mechanical properties of corroded bars, 1,2 time to cracking of concrete, [3][4][5] bond-slip relationships, [6][7][8] probabilistic service life prediction of corroded RC members, [9][10][11] effects of corrosion on the structural capacity of concrete members by considering either uniform or pitting corrosion, [12][13][14][15] and corrosion repair techniques. 16,17 However, in situ data collections by considering all the effects of corrosion are complex.…”
Section: Introductionmentioning
confidence: 99%